The Xhosa Cattle-Killing Movement in History and Literature - Offenburger, Andrew (History compass, 2009)
In South Africa’s Eastern Cape frontier zone, a millenarian movement known as the Xhosa Cattle-Killing (1856-1857) devastated local populations and stunned observers. How could the messages of its prophetess, Nongqawuse, and the exhortations of her uncle, Mhlakaza, lead to the slaughter of hundreds of thousands of cattle, to the death of tens of thousands of people, and to the subjugation of the Xhosa? Historians and authors of literary works have attempted to answer this question, and their explanations have followed the contours of South African history through three general phases. The first (1857-1947) characterized the movement as a failed revolt against British expansion and a necessary step in social and religious Darwinism. The second period (1948-1988) saw the continuation of these interpretations, and, with National Party rule and the rise of the Black Consciousness Movement, an increasingly radical group of historians brought about politicized and alternative interpretations embedded in Xhosa oral history. The third phase (1989-) began with the publication of Jeff Peires’The Dead Will Arise, which renewed interest in the history and has inspired a new wave of historical critique.